Multibeam bathymetry raw data (Atlas Hydrosweep DS 2 echo sounder entire dataset) of RV METEOR during cruise M58/3 - Meinecke, Gerrit (PANGAEA, 2025)
Raw bathymetry data were collected using Atlas Hydrosweep DS2 multibeam echosounder during the RV METEOR cruise M58/3. The cruise took place between 2003-06-11 and 2003-06-24 (Las Palmas, Spain - Ponta Delgada, Portugal). The main focus of the cruise were the ESTOC and ANIMATE oceanographic programs, as well as testing of the new ROV system QUEST 5. Bathymetry data were collected continuously during the cruise in between the Canary Islands and the Azores. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. No ancillary sound velocity profiles (SVP) data from the cruise are archived at the BSH, thus no SVP files are added to this dataset. Data are unprocessed and therefore contain incorrect depth measurements (artifacts). Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).
Keywords: Bathymetry; Multibeam Echosounder